Zasada swiatla i ciemnosci - Schmidt, Peter, 1944-; Schmidt, Peter, 1944- (Bydgoszcz : Wydawnictwo "Pomorze", 1990)
Polish translation of a German science fiction thriller.
Translation of: Das prinzip von hell und dunkel.
Keywords: Science fiction, German -- Translations into Polish